HADIS TENTANG KEIMANAN ORANG YANG BERBUAT MAKSIAT - Muhammad Nuh Siregar (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
Immoral acts or great sins committed by someone does not cause a person to become an infidel. But he is still said to be a believer despite his lowest level of faith. Because based on the Hadith of a believer's faith are multilevel and can be increased and can also be reduced. A person's faith will increase when he carries out obedience, carries out the commands of religion and carries out other goodness. Conversely, one's faith will decrease when he commits sin and or disobedience. On the basis of this, it was concluded that the faith of the theology of the Khawarij, Muktazilah and others which determined that one's faith was seen from his deeds could not be held captive. But the true faith is tasdiq (accept) in the heart that "There is no god but Allah". During his heart there is tasdiq, even though his body members commit the greatest immorality even though he is still said to have faith. However, the level of faith is the lowest level. While the most perfect faith is tasdiq in the heart, pronounced with the tongue and practiced by the limbs. For that, let's compete in doing good or obedience to Allah and His Messenger and leaving everything that is forbidden so that the faith will increase and become more perfect.